AB1248 MALHEUR PROJECT CONFIRMS SPECIFIC CHARACTERISTICS OF MALIGNANCIES IN PATIENTS WITH RHEUMATIC AND MUSCULOSKELETAL DISEASES. (June 2019) - Benesova, Karolina; Czaja, Maria; Max, Regina; Lorenz, Hanns-Martin
Abstract : Background: Both rheumatic and musculoskeletal diseases (RMDs) and malignancies are frequent in the population and the probability of simultaneous occurrence in one individual is accordingly high. However, the interrelation of malignancies in patients with RMDs is still a blind spot in rheumatology. Since both disorders present two extremes of a dysregulated immune response, their interdependencies are undoubtedly complex. There is very little reliable data on cancer and relapse risk due to a certain disease entity as well as particular disease modifying therapies. Objectives: The MalheuR project is a registry-based study that has been initiated at the university hospital Heidelberg, Germany to close this gap. Methods: In three subregistries, we address the specific situation of patients suffering from concomitant RMD and malignancy (RheuMal registry), paraneoplastic rheumatic disorders due to a malignancy (ParaRheuMa registry) and rheumatic immune-related adverse events (irAE) due to cancer immunotherapy (TRheuma registry). Herein, we present first data from RheuMal registry. Results: We analyzed 55 patients with concomitant RMDs and malignancies. The mean onset of the RMD was 58.9 years in females (n=33) and 54.2 years in males (n=22), the mean onset of the malignancy was 59.9 years and 56.3 years respectively. In patients first suffering from a RMD (n=38), the average time to malignancy diagnosis was 10.3 years [1-33 years]. Only 13 patients were diagnosed with a malignancy before RMD. 4 were diagnosed for both disorders simultaneously. Solid tumors were present in 54%, hematologic neoplasms in 17%, non-melanoma skin cancer in 21% and melanoma in 8%. 13 patients suffered from more than one neoplasm with 1 patient showing a secondary neoplasm, 4 patients with recurring skin cancer and 4 with additional benign neoplasms. Out of 6 patients pre-treated with cyclophosphamide, lymphoma, bladder and prostate cancer were diagnosed in one case each. 16 patients were pre-treated with TNFa-inhibitors, 2 cases of melanoma, 4 cases of non-melanoma skin cancer and 2 cases of hematologic neoplasms occurred. Among 7 patients with azathioprine intake, two developed non-melanoma skin cancer, but no melanoma was diagnosed. A comparison with the German cancer registry of the Robert Koch Institute suggests an earlier onset of gender specific cancers in our patients with mean onset of breast cancer (n=5) 5.2 years and prostate cancer (n=8) 7.0 years earlier. Furthermore, in males with RMDs melanoma occurred 8.4 years earlier (n=5), but squamous cell skin cancer was diagnosed 12.2 years later than in the reference cohort. Conclusion: Overall, our data show specific characteristics of malignancies in RMD patients suggesting a different cancer epidemiology compared to overall population. Disclosure of Interests: Karolina Benesova Grant/research support from: Scientific Projects (IIT) I'm involved in as an investigator have been supported, but not initiated or designed by Abbvie and Novartis, Consultant for: Advisory board member on early disease detection for Novartis, Maria Czaja: None declared, Regina Max: None declared, Hanns-Martin Lorenz: None declared